Multidimensional Effects of Family Environment on Primary Students’ Achievement: Insights from Kupang, Indonesia - Heryon Bernard Mbuik; Rismawaty Djawa Ratu; Roswita Lioba Nahak (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2026)
This study investigates the influence of the family environment on students’ learning achievement, focusing on Grade IV students at SD Inpres Oesapa Kecil 1, Kupang, Indonesia. Employing a descriptive quantitative approach, the study explores the roles of parental attention, educational support, home learning atmosphere, and motivation. Data were gathered through structured questionnaires administered to 30 students and analyzed using descriptive statistics, including frequency, percentage, and mean. The results reveal that the family environment has a significant and positive influence on students’ academic achievement. Educational support emerged as the most impactful factor, followed by parental attention and motivation, while the home learning atmosphere remained slightly lower but still within the high category. The study underscores the critical role of active family involvement and collaborative efforts between parents and schools to enhance learning outcomes.